Dialektika Unsur Merintangi Kegiatan Usaha Pertambangan Dengan Prinsip Demokrasi - Haryadi, Dwi; Rahayu, Sri; Satrio, Ndaru (PROGRESIF: Jurnal Hukum, 2023)
The element of "obstructing or interfering with mining business activities" is the focus of this article, because the editorial has multiple interpretations. Its existence derives two problem formulations, namely (1) What are the problems with elements hindering or interfering with mining business activities?: (2) What is the reformulation that reflects democratic principles? The analytical knife used to examine existing problems through democratic principles. This study uses normative juridical research methods. There are several conclusions related to the problematic presence of elements hindering or interfering with mining business activities, including: first, elements hindering or interfering with mining activities can be directed to actions that can be interpreted differently. Second, these elements can be directed to certain interests. Third, these elements can be subjective. Fourth, it is counterproductive to provisions for environmental fighters who cannot be sued criminally or civilly. The reformulations that are expected to better reflect democratic principles include: first, providing a more detailed explanation regarding the redaction of elements hindering or disrupting mining activities. Second, changing the editorial elements hinders or disrupts mining business activities. Third, remove the redaction elements that hinder or interfere with this mining business activity.